POST-TIKTOK SHOP CLOSE DOWN: WILL MSMEs REALLY RISE IN INDONESIA? - Solihati, Keisha Dinya; Wati, Nila Kurnia; Herawati, Augustin Rina; Sari, Novieta Hardeani (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
TikTok is ranked 1st place in the period from January to December 2022. There have been suspicions over TikTok's efforts to further prosper its business through an initiative called Project S via TikTok Shop. Therefore, recently the government established Regulation of the Minister of Trade of the Republic of Indonesia Number 31 of 2003. With this policy, TikTok Shop stopped operating on October 4, 2023 due to violations of socio-commerce rules. This study aims to explore perspectives related to post-closure policies of TikTok Shops in relation to supporting the sustainability of MSMEs in Indonesia. This research uses a qualitative descriptive research method with phenomenology and case study approach. Data collection techniques through interviews with MSMEs and TikTok Shop users and literature studies. It is concluded that although the weakening of the conventional MSME market is not necessarily caused by e-commerce only, this policy is considered a good step to be taken to anticipate the threat of rampant trade from abroad that can threaten Indonesian MSMEs. MSMEs that have indeed utilized the TikTok Shop feature will still be able to use TikTok as a social media service for promotional means, only the transactions will be connected to other platforms.